2003
DOI: 10.1090/s0894-0347-03-00419-3
|View full text |Cite
|
Sign up to set email alerts
|

Multivariable cochain operations and little 𝑛-cubes

Abstract: In this paper we construct a small E ∞ E_\infty chain operad S \mathcal {S} which acts naturally on the normalized cochains S ∗ X S^*X of a topological space. We also construct, for each n n , a suboperad S n \mathcal {S}_n which is quasi-isomorphic to the normalized singular chains of the little n n -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
162
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(166 citation statements)
references
References 18 publications
2
162
0
2
Order By: Relevance
“…This operad is also introduced (with different sign conventions) by J. McClure and J. Smith in their work on the Deligne conjecture (cf. [22,23]). To be precise, the Barratt-Eccles operad E operates on cochain complexes of simplicial sets and on Hochschild complexes of associative algebras through a morphism T R: E →X which we call the table reduction morphism.…”
Section: Introductionmentioning
confidence: 99%
“…This operad is also introduced (with different sign conventions) by J. McClure and J. Smith in their work on the Deligne conjecture (cf. [22,23]). To be precise, the Barratt-Eccles operad E operates on cochain complexes of simplicial sets and on Hochschild complexes of associative algebras through a morphism T R: E →X which we call the table reduction morphism.…”
Section: Introductionmentioning
confidence: 99%
“…The first part of this is immediate. For the second we construct the stabilization via a colimit whose maps actually add topology to the pieces p and explicitly give the E ∞ operations as the geometrization of the operations of [9]. If A is not semi-simple the action does not pass through the stabilization.…”
Section: Some Details On the Action Relevant To The Further Discussionmentioning
confidence: 99%
“…Proof. (i) ⇒ (ii): In [Rickard 1991], it is shown that and admit a standard derived equivalence. Thus there is a bounded complex P of --bimodules which in each degree is finitely generated projective over and over .…”
Section: (I)mentioning
confidence: 98%
“…The classical Morita theory for derived categories [Rickard 1989;1991] can be extended to complexes of injective modules as follows.…”
Section: A Recollement For K(inj Kg)mentioning
confidence: 99%